Doing CLIL in the Science Classroom: a Critical Sociolinguistic Ethnography in La Mancha Secondary Schools - Alicia Fernández-Barrera (FahrenHouse, 2019)
This study examines CLIL (Content and Language Integrated Learning) science education in two bilingual (Spanish/English) schools in Castilla-La Mancha (Spain), a region which has recently implemented «Bilingual or Plurilingual Projects» under the provisions of the new «Integral Plan of Foreign Language Teaching in Castilla-La Mancha». By taking a critical sociolinguistic ethnographic perspective, the article explores how CLIL is understood and accomplished in an actual science classroom through English as the medium of instruction. This empirical approach serves as the framework to reflect upon the pedagogical transformation of traditional core areas, such as science, and the ideologies circulating among science teachers regarding their own practice. By looking into interactional events in situated classroom practices, the analysis sheds light on three key issues: 1) the role of language(s) in the process of meaning-making negotiation; 2) the way content is organised, taught and acquired through English; and 3) how teachers and students construct both academic and linguistic knowledge. From a CLIL perspective, the study examines daily teaching and learning practices and how teachers struggle to appropriate this methodology to integrate content and language while facing multiple institutional, pedagogical, logistics and behavioural challenges in the science classroom. Data comprise CLIL science interactions in two 1st grade of compulsory secondary education (CSE) classrooms at two state-funded private bi/plurilingual schools in La Mancha City (pseudonym), as well as semi-structured interviews carried out with the science teachers involved in the bilingual programme. For this purpose, the CSE lens contributes to better understand how CLIL science education works by establishing links between language policies, teachers' ideologies and situated practices in relation to wider social processes.